Conservation and Sustainability of Sowang Plant: Does Folk Taxonomy Play an Important Role? - Sanito, Raynard Christianson (Prosiding SNPBS (Seminar Nasional Pendidikan Biologi dan Saintek), 2022)
Sowang (Xanthostemon novoguineensis Valeton) plays an important role in supporting the life of local communities in Papua. Sowang, the endemic plant from Papua Province, Indonesia, has faced the high issues related to land conversion, forest burning, and logging, where this plant can be found in Cyclops mountain. This paper gives the information on the important role of folk taxonomy, which is associated with the sustainability of Sowang in their natural habitat. The study of folk taxonomy plays a significant role in identifying Sowang in their natural habitat by the local communities. Furthermore, the exploration of this study in the field can be conducted to understand the function, distribution and population in their natural habitat. After that, the strategies for protecting this plant can be implemented, involving governments, researchers and local communities. Further studies associated with the folk taxonomy should be implemented for the conservation of Sowang for the sustainabilityof this plant in Papua.